Neonatal eyelid penetration from insertion of a fetal scalp electrode: a case report - Brian T. Cheng; Kelly D. Laurenti; Sudhi P. Kurup (BMC, 2022)
Abstract Background A fetal scalp electrode (FSE), first described by Edward Hon in 1967, is an intrapartum monitoring device embedded directly into the fetal scalp for an accurate measure of fetal heart rate. Though use of an FSE is generally safe, complications can occur from misplacement, including ophthalmic injury. Case presentation Patient was a 28-year-old G6P5006 who presented for induction of labor at 39 weeks due to asymptomatic bilateral pulmonary embolism. Concerning findings on external fetal monitoring led to placement of a fetal scalp electrode for close monitoring. Upon delivery, the neonate was noted to have the FSE embedded in the left upper eyelid. Ophthalmology was consulted and could not rule out ocular injury on external examination at the bedside. Examination under anesthesia in the operating room demonstrated no penetration of the ocular globe, and the eyelid laceration was sutured. The laceration was well-healing at one-week follow-up with no further complications. Conclusion Facial or brow presentation during delivery is rare but may increase the risk for misplacement of an FSE. Ultrasound verification of vertex position is warranted immediately prior to placing an FSE for patients at higher risk of facial or brow presentation. Periorbital edema of neonates may protect against damage to deeper structures. However, Ophthalmology should be consulted to rule out ocular injury if the FSE is placed in the periocular region.